2009
DOI: 10.1111/j.1524-4725.2009.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Photodynamic Therapy Does Not Prevent Recurrence of Condylomata Acuminata After Carbon Dioxide Laser Ablation—A Phase III, Prospective, Randomized, Bicentric, Double-Blind Study

Abstract: Adjuvant ALA-PDT of CA after CO(2) laser ablation was well tolerated, but no significant difference with regard to recurrence rate was observed from CO(2) laser vaporization alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 15 publications
0
36
0
3
Order By: Relevance
“…Moreover the proportion of patients with adverse effects in ALA–PDT group was also significantly lower than the CO 2 laser group. However Szeimies et al 44 did not find any difference in recurrence rates when ALA–PDT was combined with CO 2 laser. Topical ALA and red light (630 nm) was used to treat genital condylomata in nine men who had at least one unsuccessful conventional treatment.…”
Section: Pdt Of Viral Lesionsmentioning
confidence: 90%
“…Moreover the proportion of patients with adverse effects in ALA–PDT group was also significantly lower than the CO 2 laser group. However Szeimies et al 44 did not find any difference in recurrence rates when ALA–PDT was combined with CO 2 laser. Topical ALA and red light (630 nm) was used to treat genital condylomata in nine men who had at least one unsuccessful conventional treatment.…”
Section: Pdt Of Viral Lesionsmentioning
confidence: 90%
“…The side-effects in patients treated with ALA-PDT mainly included mild burning and/or stinging restricted to the illuminated area. However Szeimies et al (120) reported no difference in recurrence rates when ALA-PDT was combined with CO 2 laser. Herzinger et al (121) performed a small open study using topical 5-ALA and red light (630 nm) in nine men with genital condylomata and a history of at least one previous unsuccessful conventional treatment.…”
Section: Pdt For Clinical Infectious Diseasementioning
confidence: 99%
“…The advantage continues to be the ability to treat a large surface area, and with minimal scarring. In terms of recurrence rates, it is unclear whether PDT or CO 2 laser therapy is superior 133,136…”
Section: Pdt In Microbial Diseasesmentioning
confidence: 99%